Embedded components design strategy framework for fuse deposition modeling system - Heng, Khim Hiong (2022)
The aim of this project is to develop a framework to guide the process of 3D printing embedded products specifically by using fused deposition modeling (FDM) printing process. Furthermore, to meet the environmental sustainability, the framework also focusses on the material use to create product which allow the user to recycle the products. In this project, the framework was used as a technique to improve the design of the product by lowering the number of components and assemblies. The framework was developed in four-layered design criteria to overcome the difficulties of embedded products design which includes Design Process Flow, Design Knowledge, Key Enabling Technologies, and Design Application. Three case study were used which are Electric Shaver, Remote Control and Nintendo Switch to compare the robustness and the effectivenss of the framework. Based on first case study, it was able to design a product with integration for blade interchangeable. While for the second case study, the compatibility to change the cover with similar size which allow it to be reusable. In third case study, it shows the flexibility of the design which every single part is interchangeable with various looks and design that allow the user to independently change to the desired pattern without the help from the external that will lead to cost incur. In other words, there are disadvantages in the development after using the framework. First case study shows that the design is too bulky and difficulty to monitor on the blade life span. As for the second case study, the development was not able to create a water-resistant product and also the battery indicator of batter life span. Third case study, shows that the pixel resolution during usage of the product is not satisfactory. The framework gives many advantages than disadvantages to the development whereby time constraint, cost and resources are reduced significantly. Lastly, this project shows a simplified study of the FDM process which aids in minimizing waste and difference of current market design with the new design by using framework.